Structure and activities of the eukaryotic RNA exosome - Wasmuth, Elizabeth V. (Enzymes, 2012)
The composition of the multisubunit eukaryotic RNA exosome was described more than a decade ago, and structural studies conducted since that time have contributed to our mechanistic understanding of factors that are required for 3′-to-5′ RNA processing and decay. This chapter describes the organization of the eukaryotic RNA exosome with a focus on presenting results related to the noncatalytic nine-subunit exosome core as well as the hydrolytic exo- and endoribonuclease Rrp44 (Dis3) and the exoribonuclease Rrp6. This is achieved in large part by describing crystal structures of Rrp44, Rrp6, and the nine-subunit exosome core with an emphasis on how these molecules interact to endow the RNA exosome with its catalytic activities.